2014
DOI: 10.5812/hepatmon.17641
|View full text |Cite
|
Sign up to set email alerts
|

Nonalcoholic Fatty Liver Disease/Non-Alcoholic Steatohepatitis in Childhood: Endocrine-Metabolic “Mal-Programming”

Abstract: Context:Nonalcoholic Fatty Liver Disease (NAFLD) is the major chronic liver disease in the pediatric population. NAFLD includes a broad spectrum of abnormalities (inflammation, fibrosis and cirrhosis), ranging from accumulation of fat (also known as steatosis) towards non-alcoholic steatohepatitis (NASH). The development of NAFLD in children is significantly increased.Evidence Acquisition:A literature search of electronic databases was undertaken for the major studies published from 1998 to today. The database… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 73 publications
(101 reference statements)
0
14
0
Order By: Relevance
“…A reduction of GSL biosynthesis in the adipose tissue of ob/ob mice restored insulin signaling in isolated ex vivo insulinstimulated adipocytes (168,172,176). The improved adipogenesis was a result of the reduced number of larger adipocytes and increased expression of PPAR␥, insulin-responsive glucose transporter (GLUT)-4, and adipsin (103,107,168,169,172,176). Adiponectin gene expression and protein were increased by AMP-DNM, leading to a decreased inflammation in adipose tissue.…”
Section: Glucosylceramide Synthase Inhibitors and Other Inhibitors Ofmentioning
confidence: 86%
See 3 more Smart Citations
“…A reduction of GSL biosynthesis in the adipose tissue of ob/ob mice restored insulin signaling in isolated ex vivo insulinstimulated adipocytes (168,172,176). The improved adipogenesis was a result of the reduced number of larger adipocytes and increased expression of PPAR␥, insulin-responsive glucose transporter (GLUT)-4, and adipsin (103,107,168,169,172,176). Adiponectin gene expression and protein were increased by AMP-DNM, leading to a decreased inflammation in adipose tissue.…”
Section: Glucosylceramide Synthase Inhibitors and Other Inhibitors Ofmentioning
confidence: 86%
“…Aspartyl-asparaginyl-␤-hydroxylase (AAH) mediates its effect by activating Notch. Insulin/IGF signaling, AAH, and Notch are inhibited in ALD (99,103,146). Chronic ethanol-fed rats had shown an increased Cer levels and steatohepatitis, with impairments in insulin receptor signaling, insulin receptor substrate, and Akt.…”
Section: Altered Cer Levels Affect Liver Steatosis and Insulin Resistmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, Peng et al (8) showed that the liver expressed the highest levels of betatrophin in humans, whereas expression was lower in adipose tissue and skeletal muscle. Additional studies demonstrated that hyperinsulinaemia could accelerate NAFLD in obesity, which subsequently might result in insulin resistance via mechanisms including inflammation and unsaturated fatty acids (24,32,33). Moreover, the prevalence of NAFLD in the insulin-resistant group was significantly higher than that in the non-insulin-resistant group.…”
Section: Discussionmentioning
confidence: 99%